ナンキョク ニ オケル セイソウケン トツゼン ショウオン ゲンショウ ト ウチュウセン - 井上, 葵; イノウエ, アオイ; 小玉, 正弘; コダマ, マサヒロ; INOUE, Aoi; KODAMA, Masahiro (国立極地研究所, 1967)
P(論文) Using the data from Mawson, Antarctica, seven sets of partial temperature coefficients of the cosmic ray meson component, recommended by DORMAN and other authors, were examined on the basis of regression calculation analysis. The phenomenon of stratospheric sudden warming, which frequently appears in polar regions, is convenient for studying the atmospheric effect of cosmic rays, because the altitude dependence of the atmospheric temperature is largely different from that of usual days. The temperature coefficients by DORMAN, by MAEDA and by WADA fit better with the observational results of all seven sets. It shows that the upper atmospheric temperature, which is difficult to measure continuously, may be presumed from the cosmic ray intensities on the ground, if the accuracies of the cosmic ray data and of the lower atmospheric temperatures are more than 107 counts per hour and 0.1℃, respectively. This estimation will be referred to in the forthcoming extension of the cosmic ray observations in Antarctica. departmental bulletin paper